National Law: Sharia Law as an Instrument for Protecting Human Rights (HAM) in Islam - Nst, Abdul Saman (Jurnal Hukum dan Keadilan, 2025)
Human Rights (HAM) are fundamental rights inherent in every individual since birth without distinction of ethnicity, religion, race, or social status. The principle of universality and justice in human rights has long been part of Islamic teachings through sharia law (al-syariah al-islamiyyah). Sharia not only regulates aspects of religious rituals, but also includes a comprehensive legal system that guarantees human welfare and dignity. The main objective of sharia law is realized in the concept of maqāṣid al-syarī‘ah, which includes protection of religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), reason (ḥifẓ al-‘aql), descendants (ḥifẓ al-nasl), and property (ḥifẓ al-mal). These five principles represent the essence of human rights in Islam, showing the harmony between Islamic values ​​and modern human rights principles as stated in the Universal Declaration of Human Rights (UDHR) 1948. This research uses a literature review method, examining primary and secondary sources related to Sharia law and human rights. The results indicate that Sharia law serves as a normative, moral, and social instrument in protecting basic human rights and has strong relevance to contemporary human rights principles. However, implementation challenges arise from differences in Sharia interpretations, partial application, and a lack of integration between the values ​​of Sharia's objectives and national law. Therefore, a harmonious approach is needed that integrates Islamic values ​​of justice and welfare with the positive legal system to strengthen comprehensive human rights protection.